Energy Efficiency Assessment of the Use of Expander-Generator Set in Cogeneration Systems - Gubarev V. Ia.; Arzamastsev A. G.; Sharapov A. I.; Kartel A. Iu. (Problems of the Regional Energetics, 2018)
. The purpose of the article is to assess energy efficiency of the expander generator application in cogeneration systems. It demonstrates that the research works devoted to this subject do not take into account the effect that gas parameters after the expander have on operating efficiency of the main power generating equipment that leads to a distortion of the assessment of expander energy efficiency. The energy efficiency is determined by specific fuel savings resulting from the use of a circuit with an expander compared to the option of gas throttling. It shows that spe-cific fuel saving is directly proportional to the increment value of the total specific useful work of the utility company when using expander generators. It was found that when using the ex-pander at the cogeneration plant the total specific useful work increment is less than the specific work of the expander generator. It is shown that the energy effect magnitude from the use of circuits with an expander at cogeneration boilers depends on the ambient air temperature. For an expander at cogeneration boiler houses with gas piston internal combustion engines at air tem-peratures below the optimum mixture temperature, the total increment of the specific work is equal to the specific work of the expander, at higher temperatures, the increment of the total specific work can be several times greater than the specific work of the expander. The prospects of preheating gas before the expander at the considered utility companies were analyzed.